Isolation of a rearranged human transforming gene following transfection of Kaposi sarcoma DNA. - Delli Bovi, P (1987)
By transfecting high molecular weight DNA from a Kaposi sarcoma lesion into murine NIH 3T3 cells, we have identified and molecularly cloned a set of human DNA sequences capable of inducing focus formation, growth in agar, and tumorigenicity in these cells. The human DNA sequences present in primary, secondary, and tertiary NIH 3T3 transformants encompass about 32 kilobases (kb) and contain four rearrangements with respect to normal human DNA and a portion of the c-fms protooncogene (FMS in human gene nomenclature). However, the minimal transforming region (6.6 kb) identified in our cloned DNA borders on the c-fms DNA region but does not contain c-fms coding sequences. The fms sequences are also not represented in the two transcripts (approximately equal to 1.2 and 3.5 kb) detected in NIH 3T3 transformants; however, they might provide elements regulating expression. Hybridization to several known oncogene probes and preliminary sequencing data indicate that we have identified a previously unrecognized "activated" oncogene. Since the rearrangements present in our cloned DNA sequences are not detectable in the original Kaposi tumor DNA used for transfection, it is possible that this oncogene was generated during gene transfer.